До питання композиції багатотомних видань творів Івана Франка - Голяк, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
Today due to the problems with the preparation of academic publication of Ivan Franko’s works the question of material organizing principles tends to be of particular practical significance. In this article we focus on the issue of already existing multivolume editions’ composition and make some suggestions for the next scientific edition of Ivan Franko’s works.